Genetic Substrate Reduction Therapy for Mucopolysaccharidoses type III: toward a siRNA-containing nanoparticle targeted to brain cells - Coutinho, Maria Francisca (2020)
The classical therapeutic approach for LSDs, enzyme replacement therapy, would hardly rise as a potentially successful tool to reduce the disease burden in MPS III patients, as it is long known to have no impact on neuropathology. A tempting alternative, however, would be to block substrate accumulation upstream, by decreasing its synthesis. That concept is known as substrate reduction therapy (SRT). Having this in mind, we designed an RNA-based strategy based upon the selective downregulation of one gene involved in the very early stages of the glycosaminoglycans’ (GAG) biosynthethic cascade. Our goal is to promote an effective reduction of the accumulating substrate, ultimately decreasing or delaying MPS’ symptoms. As tools to achieve substrate reduction, we are evaluating a specific type of antisense oligonucleotides, able to trigger a naturally-occurring post-transcriptional gene silencing process called RNA interference: the small interfering RNAs (siRNAs). So far, the obtained results are quite promising with marked decreases of the target mRNA levels in fibroblast cell lines for all the different MPS III disease sub-types. Initial studies addressing the overall storage of sulphated GAGs used either the routine alcian blue or a modified, more sensitive 1,9-dimethylmethylene blue assay at different time points. Nevertheless, the low confluency levels required for siRNA transfection did not allow detection of GAGs excreted to the culture media. Similar problems have been noted by other authors, including over- and under-estimation of sulphated GAGs. This is particularly relevant in small samples, like the ones we have been using. In fact, even the direct assessment of the intralysosomal suphated GAGs on those samples, while more reliable, does show some limitations. That is why we are currently implementing a novel, more sensitive method for GAG detection by liquid chromatography and quantification with electrospray ionization–tandem mass spectrometry (Saville et al., 2018). Thus, additional data on the effect of the designed siRNAs on substrate accumulation will be collected over the next months and other methods will be used to further address this issue. Here we present an overview on the current results of this project, while discussing its’ next steps, namely the development and evaluation of vectors for in vivo delivery. Our goal is to develop targeted stable nucleic acid lipid particles (t-SNALPs) coupled with different ligands, which promote cell uptake of the ‘anti-GAG’ siRNAs in a variety of cells, including neurons.